2014
DOI: 10.7860/jcdr/2014/9014.4680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Examination Stress and Its Effect on Cognitive Function among First Year Medical Students

Abstract: Background: Medical students experience stress at every phase of curriculum more so before examination. This stress may affect physiological, psychological and cognitive functions of the students. Aim:The present study aimed to evaluate stress status among first year MBBS students by recording pulse rate (PR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and using stress questionnaire; its effect on cognitive function by recording auditory reaction time (ART) and visual reaction time (VRT). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The influence of stress on hearing abilities can be seen in people (Pradhan et al, 2014 ) and in experimental animals (Muchnik et al, 1980 ; Dagnino-Subiabre et al, 2005 ; Mazurek et al, 2010 ). The majority of findings suggest development of hearing impairment following stressful situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of stress on hearing abilities can be seen in people (Pradhan et al, 2014 ) and in experimental animals (Muchnik et al, 1980 ; Dagnino-Subiabre et al, 2005 ; Mazurek et al, 2010 ). The majority of findings suggest development of hearing impairment following stressful situations.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional stress is also known to associate with various hearing conditions such as sudden hearing loss, Meniere's disease, tinnitus, or hyperacusis (Rauschecker et al, 2010 , 2015 ; Mazurek et al, 2012b ). Moreover, acute stress increases auditory reaction times in healthy young people (Pradhan et al, 2014 ) and in healthy and autistic children (Fujikawa-Brooks et al, 2010 ), suggesting close interactions between stress response and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is especially the examination phase in which students could profit from good stress-buffering abilities, as high amounts of perceived stress are known to diminish cognitive functioning in students [ 13 ], which in turn is highly correlated to AP [ 14 ]. Studies revealed significant negative correlations between perceived stress and AP in students, especially within examination periods at the end of a semester [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Threat response to a stressor, as found in a cold pressor test, may impair memory retrieval [3], which appears crucial to exam-passing rate [1]. Indeed, preexamination distress in medical students was found to impair cognitive function [4] and to predict poor academic performance [5][6][7]. Medical students tend to be more stressed than their peers, and academic examinations represent a significant source of this stress [5,8].…”
Section: Introductionmentioning
confidence: 99%